Associations between Sclerostin and Anthropometric and Metabolic Parameters in Children and Adolescents - Shin-Hee Kim; Yun Jung Choi; Moon Bae Ahn; Won Kyoung Cho; Kyoung Soon Cho; Min Ho Jung; Byung-Kyu Suh (MDPI AG, 2021)
(1) Background: Bone plays an important role in the regulation of the systemic glucose and energy metabolism. Sclerostin, secreted by osteocytes, is an inhibitor of the Wnt/β-catenin bone metabolic pathway, and is involved in osteoporosis and metabolic disease. The aim of this study was to investigate the relationship between sclerostin and anthropometric and metabolic parameters in children and adolescents with obesity or who are overweight. (2) Methods: This study included 63 children and adolescents (20 obese, 11 overweight and 32 healthy control subjects). We evaluated the correlation between serum sclerostin and anthropometric parameters, metabolic parameters related to glucose (homeostasis model assessment of insulin resistance [HOMA-IR]), lipid, and bone metabolism (osteocalcin and 25-hydroxy vitamin D). (3) Results: Sclerostin and osteocalcin levels did not differ between obese and control groups. Sclerostin level was higher in boys than in girls (median 20.7 vs. 18.9 pmol/L, respectively; p = 0.04). In all subjects, sclerostin levels were negatively correlated with fasting insulin (r = −0.26; p = 0.04) and HOMA-IR (r = −0.28; p = 0.03), and positively correlated with serum concentrations of triglycerides (r = 0.29; p = 0.04), alkaline phosphatase (r = 0.41; p = 0.002), and osteocalcin (r = 0.33; p = 0.008). In obese patients, sclerostin levels were correlated negatively with fasting glucose (r = −0.49; p = 0.03) and HOMA-IR (r = −0.48; p = 0.03) and positively correlated with triglyceride levels (r = 0.53; p = 0.02). In the healthy control, sclerostin levels were correlated negatively with fasting insulin levels (r = −0.61; p < 0.001) and HOMA-IR (r = −0.36; p = 0.04). After adjusting for age, sex, and height SDS, a negative correlation between sclerostin and HOMA-IR was found (r = −0.39; p = 0.003) in all of the subjects. This association was more evident in obese patients (r = −0.60; p = 0.01) than in healthy controls (r = −0.39; p = 0.047). (4) Conclusions: Among children and adolescents with obesity, serum sclerostin was negatively correlated with HOMA-IR. Further studies are needed to clarify the mechanisms involved to understand how sclerostin affects the glucose metabolism.